2014
DOI: 10.1007/s00125-014-3162-7
|View full text |Cite
|
Sign up to set email alerts
|

Single injections of apoA-I acutely improve in vivo glucose tolerance in insulin-resistant mice

Abstract: Aims/hypothesisApolipoprotein A-I (apoA-I), the main protein constituent of HDL, has a central role in the reverse cholesterol-transport pathway, which together with the anti-inflammatory properties of apoA-I/HDL provide cardioprotection. Recent findings of direct stimulation of glucose uptake in muscle by apoA-I/HDL suggest that altered apoA-I and HDL functionality may be a contributing factor to the development of diabetes. We have studied the in vivo effects of short treatments with human apoA-I in a high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 10 publications
(16 reference statements)
2
39
0
2
Order By: Relevance
“…HFDfed mice received a glucose load (50 mg/mouse i.p. ), with or without propranolol (5 mg/kg) and epinephrine (0.1 mg/kg), to block insulin secretion, 3 h after a single injection (14 mg/kg body wt) of apoA-I protein or NaCl control followed by the determination of glucose (C) and insulin (E) Short-term apoA-I treatment of insulin-resistant DIO mice leads to a remarkable increase in blood glucose clearance (9).…”
Section: Resultsmentioning
confidence: 99%
“…HFDfed mice received a glucose load (50 mg/mouse i.p. ), with or without propranolol (5 mg/kg) and epinephrine (0.1 mg/kg), to block insulin secretion, 3 h after a single injection (14 mg/kg body wt) of apoA-I protein or NaCl control followed by the determination of glucose (C) and insulin (E) Short-term apoA-I treatment of insulin-resistant DIO mice leads to a remarkable increase in blood glucose clearance (9).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, treatment with HDL or apoA-I increases insulin secretion and production in isolated pancreatic islets and insulinoma beta cell lines [7,8]. Recent studies have demonstrated that both single and repeated doses of apoA-I can also improve insulin resistance in fat-fed C57Bl6 mice [9,10], as can overexpression of apoA-I [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, this association has not been found to be consistent in previous studies [22][23][24][25] although previous research suggested that ApoA1 affects glucose metabolism via multiple mechanisms, including enhanced insulin secretion [26], increased insulin-independent glucose uptake in muscle and adipose tissues [27,28], improved insulin sensitivity [29], and reversed adipocyte dysfunction [30] and restored adiponectin expression and insulin sensitivity [31] with ApoA1 mimetic peptide. Furthermore, genetic studies suggested that genetic variation in ABCA1 has been associated with the increased risk of T2DM [32], and one study suggested that loss-of-function mutations in ABCA1 were associated with impaired b-cell function, but not with the development of T2DM [33].…”
Section: Discussionmentioning
confidence: 51%